2002
DOI: 10.1177/002215540205001114
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Matrix Assembly Induced by Critical Assembly Concentration (CAC)

Abstract: L-2 cells are an immortalized cell line derived from yolk sac parietal endoderm cells, which are responsible for the production of Reichert's membrane, a thick basement membrane produced during rat gestation. Although the L-2 cells secrete all the major components of the basal lamina, they do not assemble a robust matrix in cell culture. We hypothesized that the reason L-2 cells fail to assemble a matrix in cell culture is because the concentrations of matrix components necessary for this matrix assembly do no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…These experiments revealed that the acellular scaffold altered the matrisome production by increasing the proportional amount of core ECM proteins, most notably for the proteoglycans. The proportional increase of proteoglycans in the scaffolds may be a consequence of the pre-existing and organized 3D ECM structure promoting either increased production of proteoglycans or proper integration of the produced proteoglycans into the existing ECM 49 . In the monolayer cultures failure to incorporate the synthesized matrisome proteins may lead to secretion into the cell media, which was not analyzed in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…These experiments revealed that the acellular scaffold altered the matrisome production by increasing the proportional amount of core ECM proteins, most notably for the proteoglycans. The proportional increase of proteoglycans in the scaffolds may be a consequence of the pre-existing and organized 3D ECM structure promoting either increased production of proteoglycans or proper integration of the produced proteoglycans into the existing ECM 49 . In the monolayer cultures failure to incorporate the synthesized matrisome proteins may lead to secretion into the cell media, which was not analyzed in this experiment.…”
Section: Discussionmentioning
confidence: 99%